Rifting of the Southwest and West Iberia Continental Margins - Terrinha, Pedro (2019)
The West and SouthWest Margins of Iberia started their formation as intra-continental rifts during initial break up of Pangea in Triassic times. The tectono-stratigraphic record of the Algarve, Alentejo and Lusitanian basins and their offshore prolongation documents the syn-rift, post-rift and passive margin phases of the rifting process as well as three magmatic cycles of tholeiite to alkaline affinities. Although the Ocean-Continent Transition has been investigated using deep ocean drilling, seismics, gravimetry and magnetics its nature and location are still matters of debate. The tectonic inheritance of the Paleozoic Orogeny had great influence in the geometry of the rift basins and development of the Neo-Tethys and Atlantic Oceans intersection. Salt tectonics strongly controlled both syn-rift and post-rift basin tectonics and led to the formation of an allochthonous salt nappe in the Algarve Basin.